Implementasi Blended Learning dengan Media Boardgame untuk Meningkatkan Aktivitas dan Prestasi Siswa pada Materi Pernapasan Manusia - Edi Martani, Edi Martani (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
Blended Learning learning model is an innovation between technology and pedagogy, which combines synchronous and asynchronous learning. Blended learning makes teachers more empathetic, creative, empowered and involved. That is the teacher who is free to learn. Models like this are becoming a trend all over the world. Games as something that is considered fun can be used to contain educational content that can help convey positive values ​​in building human intelligence as a whole. Because games can train the brain's ability to actively, stimulate the brain in making decisions, and can solve problems at hand. The body's organ system is a material that is studied from 5th grade students to high school. However, this important material will be something less meaningful, if presented with an inappropriate strategy. Several alternative learning support media have been provided but still have shortcomings in increasing the spirit of learning. So the author tries to create a new opportunity to create learning support media, using boardgame media to increase students' enthusiasm for learning. By applying blended learning with boardgame media, it makes students more enthusiastic about learning and shows increased achievement. Students are also involved in determining learning objectives, assessment methods and learning activities. Thus creating students who are free to learn. Based on the results of the research that has been carried out, learning with a blended learning model using boardgame media has succeeded in increasing achievement and learning activities for the human respiratory system material for class 5th MI Negeri 1 Magelang. This is evidenced by the increase in classical completeness from 31.25 in the pre-cycle, to 62.5 in the first cycle and 93.75 in the second cycle.